Fibrolipomatous hamartoma of the median nerve: An outcome of surgical management in six consecutive cases - Avinash Prabhu; R Anil; Niranjan Kumar (Nigerian Journal of Surgery, 2020)
Background: Lipoma is a nonneurogenic benign tumor. Neurolipoma and fibrolipomatous hamartoma are variants of this universal tumor. All these variants are grouped under lipomatosis of the nerve. Majority of these tumors are asymptomatic, which can be observed. Symptomatic patients require surgery, which is not standardized. As there are insufficient number of cases, no randomized controlled studies have been performed in the treatment of fibrolipomatous hamartoma. The aim of our study was to determine the pattern of presentation of fibrolipomatous hamartoma, surgical management offered, and the outcome in the form of recovery and complications. Materials and Methods: This retrospective descriptive study includes six patients diagnosed with fibrolipomatous hamartoma over a period of 12 years. Patient details were collected from the medical records. Patients diagnosed of fibrolipomatous hamartoma in the hand were included. Patients with other soft-tissue tumors were excluded from the study. Out of six patients, four required excision of nerve followed by reconstruction using sural nerve graft and two underwent microsurgical dissection of neural element. Patients were instructed to take care of the operated hand during the recovery phase. Institutional physiotherapy protocol was started during the 3rd postoperative week. Follow-up period was between 1 and 3 years. Results: All the six patients were free from symptoms postoperatively. Minimal complications were noted in two patients, which were managed conservatively. Conclusion: Surgical excision of fibrolipomatous hamartoma of median nerve below elbow, with nerve dissection or with nerve reconstruction using sural nerve graft, followed by proper postoperative care and physiotherapy has proven beneficial for the patients in our study.